Identification of ribosome biogenesis genes and subgroups in ischaemic stroke - Wang, Xi; Zhang, Xiao-Yu; Liao, Nan-Qing; He, Ze-Hua; Chen, Qing-Feng (Frontiers in Immunology, 2024)
Globally, ischaemic stroke is a leading cause of death and severe disability. Given the importance of protein synthesis in the inflammatory response and neuronal repair and regeneration after stroke, and that proteins are acquired through ribosomal translation of mRNA, it has been theorised that ribosome biogenesis may have an impact on promoting and facilitating recovery after stroke.However, the relationship between stroke and ribosome biogenesis has not been investigated. In the present study, a ribosome biogenesis gene signature (RSG) was developed using Cox and least absolute shrinkage and selection operator (LASSO) analysis. We obtained a set of 12 ribosome biogenesis-related genes (EXOSC5, MRPS11, MRPS7, RNASEL, RPF1, RPS28, C1QBP, GAR1, GRWD1, PELP1, UTP, ERI3), which play a key role in assessing the prognostic risk of ischaemic stroke. We used the above 12 genes to stratify ischaemic stroke patients into high-risk and low-risk groups, and further elucidated the immune infiltration of the disease using ssGSEA, which clarified the close relationship between ischaemic stroke and immune subgroups. Importantly, risk grouping using ribosome biogenesis-related genes was also closely associated with important signaling pathways in stroke. Through bioinformatics analysis, we identified potential IS-RSGs and explored future therapeutic targets, thereby facilitating the development of more effective therapeutic strategies and novel drugs against potential therapeutic targets in ischaemic stroke.